(untitled) (KIUT Publication, 2025)
The role of modern technologies in improving the efficiency of the banking system is becoming increasingly significant. Over the past five years, the banking system of our country has undergone significant positive changes. Among them are the full-scale use of plastic cards, the elimination of the gap between cash and non-cash funds, which was considered the norm in previous years, the introduction of mobile banking applications, and other innovations.